2020
DOI: 10.1038/s41420-020-0258-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative pharmaco-metabolomic study of glutaminase inhibitors in glioma stem-like cells confirms biological effectiveness but reveals differences in target-specificity

Abstract: Cancer cells upregulate anabolic processes to maintain high rates of cellular turnover. Limiting the supply of macromolecular precursors by targeting enzymes involved in biosynthesis is a promising strategy in cancer therapy. Several tumors excessively metabolize glutamine to generate precursors for nonessential amino acids, nucleotides, and lipids, in a process called glutaminolysis. Here we show that pharmacological inhibition of glutaminase (GLS) eradicates glioblastoma stem-like cells (GSCs), a small cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 73 publications
1
68
0
Order By: Relevance
“…Glutamine can be a primary source fueling the TCA cycle (23)(24). A recent study has shown that GLS inhibitor was effective in diminishing cell growth by limiting in ux of glutamine derivatives into the TCA cycle, but this effect was only detected in the cells which have high levels of GLS, suggesting that the role of glutamine for TCA cycle is cell line-speci c (50). In this study, we used glutamine free media or GLS1 inhibitor (CB-839) to investigate the role of glutamine-TCA cycle pathway in SUM149.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine can be a primary source fueling the TCA cycle (23)(24). A recent study has shown that GLS inhibitor was effective in diminishing cell growth by limiting in ux of glutamine derivatives into the TCA cycle, but this effect was only detected in the cells which have high levels of GLS, suggesting that the role of glutamine for TCA cycle is cell line-speci c (50). In this study, we used glutamine free media or GLS1 inhibitor (CB-839) to investigate the role of glutamine-TCA cycle pathway in SUM149.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine deprivation was found to diminish the proportion of CSC-like cells in various cancers including NSCLC, pancreatic cancer, and GBM [ 212 ]. Pharmacological inhibition of GLS was also shown to be effective in eradicating the GBM stem-like cell population, which is thought to be responsible for therapy resistance and tumour recurrence [ 213 ].…”
Section: Therapeutic Opportunities Targeting Altered Ccmmentioning
confidence: 99%
“…Glutamine can be a primary source fueling the TCA cycle [22,23]. A recent study has shown that GLS inhibitor was effective in diminishing cell growth by limiting influx of glutamine derivatives into the TCA cycle, but this effect was only detected in the cells which have high levels of GLS, suggesting that the role of glutamine for TCA cycle is cell line-specific [48]. In this study, we used glutamine free media or GLS1 inhibitor (CB-839) to investigate the role of glutamine-TCA cycle pathway in SUM149.…”
Section: Discussionmentioning
confidence: 99%